STUDENTS’ MOTIVATION AND TEACHERS’ MOTIVATIONAL STRATEGY IN LEARNING ENGLISH TO THE TENTH GRADERS OF SENIOR HIGH SCHOOL - Faishol Hadi; Haris Dibdyaningsih; Rizki Ramadhan; Khoirul Ihsan (Universitas PGRI Madiun, 2022)
The aim of this research was to investigate student’ motivation and teachers' motivational strategy in learning English at tenth graders MA Maarif Grabag and SMK Islam Sudirman. To evaluate students' motivation and teachers' motivational strategy in learning English, qualitative methodologies were employed. The subjects of the research were English teachers and the tenth grade students of MA Maarif Grabag and SMK Islam Sudirman. Observation, questionnaires, and interviews were utilized to collect the data. The questionnaire results showed that students' motivation of SMK Islam Sudirman were in Moderate (Tata Boga) and Low (TKR) and MA in Moderate. The Teachers' motivational strategy was in Enough level for SMK Islam and Good for MA Maarif. The analysis obtained showed that students have various motivations. Teachers' motivational strategy was conducted by the field rather than theories. Students' motivation majority was influenced by the intrinsic factors. Teachers did not fully applied theories, and did strategy as impacted by their characteristic, experience, knowledge, and condition of school which result on students' motivation as the extrinsic factors. The suggestion on this study was teachers should know and applied theories of motivation and how to motivate students to enhance their motivation in learning English.